(untitled) (New York, 2004)
This is the third edition of a U.S. survey text praised by adopters for its lively, engaging narrative style and its careful blending of political and social history. The authors believe that students will be drawn more readily to the study of history if they are presented with an engaging narrative of past events rather than with a mere encyclopedic compendium. The strong narrative approach helps students become engaged in the many human dramas that comprise our nation's history. The third edition is about 15 percent shorter in overall length. Its narrative has been streamlined, making it even more accessible
Keywords: United Sates,Lịch sử Hoa Kỳ; history